2011
DOI: 10.1080/15397734.2011.583204
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Response of Fully Clamped Circular Steel, Copper, and Aluminum Plates Subjected to Shock Loading

Abstract: The plastic responses of clamped mild steel, copper, and aluminum circular plates subjected to blast loads are investigated. In this way, extensive experimental results concerning the variations of central deflection and natural strain distributions are presented. The effects of plate thickness, stand-off distance, and material properties on the mid-point deflection, on the deformation profile and on the natural strain distributions are considered. Moreover, the influence of impulse on the mid-point deflection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…17,33 It should be mentioned that the effect of plate width is considered in equation 17for rectangular plates, which means that introduced dimensionless number is presented for every quadrangular plates. Also, the influence of the strain rate sensitivity is added as dimensionless number in equation (17). Similarly, for a quadrangular plate subjected to localized impulsive load, the effect of charge radius is considered and the dimensionless number is rewritten as…”
Section: Empirical Modeling Based On Governing Equation Of Quadrangulmentioning
confidence: 99%
See 1 more Smart Citation
“…17,33 It should be mentioned that the effect of plate width is considered in equation 17for rectangular plates, which means that introduced dimensionless number is presented for every quadrangular plates. Also, the influence of the strain rate sensitivity is added as dimensionless number in equation (17). Similarly, for a quadrangular plate subjected to localized impulsive load, the effect of charge radius is considered and the dimensionless number is rewritten as…”
Section: Empirical Modeling Based On Governing Equation Of Quadrangulmentioning
confidence: 99%
“…In this approach, some dimensionless numbers based on Buckingham p theory 32 have been presented to study plastic response of plates and beams subject to dynamic loading. [7][8][9]17,25,33 In a recent study, Yao et al 25 suggested a new dimensionless number for square plates subjected to only blast loading with the aid of plastic explosive.…”
Section: Introductionmentioning
confidence: 99%
“…So, for deriving empirical equations, SVD approach is used in connection with the dimensionless groups, which is incorporated in the process. 37,38 The formal definition of modeling is to detect a mathematical functionf that may be close to real one f ð Þ, in order to predict outputŷ ð Þ to its real output y ð Þ as near as conceivable for a given input vector…”
Section: Theoretical Analysismentioning
confidence: 99%
“…4,[11][12][13][14][15] Also, empirical equations based on non-dimensional analysis were reported by various researchers for computing maximum deflection of circular and rectangular plates subjected to both locally and uniformly distributed impulsive loads. 14,[16][17][18][19][20][21] In these investigations, the effects of plate geometries, material property, strain rate sensitivity and different types of loading were studied. However, less experimental and theoretical works have been performed to realize the mechanical behavior of plates under low velocity impact loading.…”
Section: Introductionmentioning
confidence: 99%